2021
DOI: 10.3390/ijms22020835
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Psilocybin Increases Synaptic Density and Decreases 5-HT2A Receptor Density in the Pig Brain

Abstract: A single dose of psilocybin, a psychedelic and serotonin 2A receptor (5-HT2AR) agonist, may be associated with antidepressant effects. The mechanism behind its antidepressive action is unknown but could be linked to increased synaptogenesis and down-regulation of cerebral 5-HT2AR. Here, we investigate if a single psychedelic dose of psilocybin changes synaptic vesicle protein 2A (SV2A) and 5-HT2AR density in the pig brain. Twenty-four awake pigs received either 0.08 mg/kg psilocybin or saline intravenously. Tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 43 publications
(27 reference statements)
6
95
1
1
Order By: Relevance
“…A recent study showed that an analogue of ibogaine, a psychedelic with differing molecular targets from psilocybin, increases spine formation rate in mice (Cameron et al, 2020). Finally, in the pig, psilocybin administration was associated with higher binding of a presynaptic protein tracer in positron emission tomography (Raval et al, 2021). Although these studies provided clues linking serotonergic psychedelics to structural and functional neuroplasticity, significant gaps remain.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that an analogue of ibogaine, a psychedelic with differing molecular targets from psilocybin, increases spine formation rate in mice (Cameron et al, 2020). Finally, in the pig, psilocybin administration was associated with higher binding of a presynaptic protein tracer in positron emission tomography (Raval et al, 2021). Although these studies provided clues linking serotonergic psychedelics to structural and functional neuroplasticity, significant gaps remain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to density (B max ), the apparent affinity (K d value) was sensitive to the residual presence of antipsychotic drugs, although this effect was only observed for [ 3 H]LSD binding assays. The finding reasserts the use of agonist radiotracers to better detect the 5-HT 2A R occupation by psychedelic drugs 46 . Receptor exploration in drug-free conditions is more feasible by PET imaging than by retrospective post-mortem binding studies.…”
Section: Discussionmentioning
confidence: 77%
“…Recent work shows that a single dose of psilocybin ( 2 ) at a presumably hallucinogenic dose (0.1 mg/kg, i.v.) reduced by up to 50% the cortical abundance of 5HT 2A binding sites labelled in vitro with [ 3 H]-MDL100907 or [ 3 H]-Cimbi-36 [ 108 ]. Other examinations in the same pig brain samples with the synaptic vesicle protein 2A (SV2A) ligand [ 3 H]-UCB-J showed a significant 5–10% increase in synaptic density in hippocampus, occurring in association with the down-regulation of serotonin receptors.…”
Section: Molecular Imaging Studies In Vivo With Hallucinogensmentioning
confidence: 99%